Shared vision based teamwork cohesiveness: catalyst for organizational commitment and organizational citizenship behavior - Ahmad Amiruddin; Yohanis Rongre; Sudirman Sudirman; Abdul Malik (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
his paper reviews the important role of Shared Vision Based Teamwork Cohesiveness (SVBTC) in bridging Organizational Commitment (OC) and Organizational Citizenship Behavior (OCB) for employees of an organization. This study was conducted using a library research method based on theoretical studies and references to reputable scientific journal articles. The study concepts include perceived organizational support (POS), organizational commitment (OC), shared vision based teamwork cohesiveness (SVBTC), and organizational citizenship behavior (OCB). The study was carried out with systematic steps which included: determining concepts and building logic between concepts, building study models, setting criteria for articles from reputable journals, and selecting articles in journals that meet the criteria Based on the results of the study conducted, we conclude that efforts to create employee OCB must begin with presenting good POS first, then good POS will encourage an increase in OC, so that it has a positive impact on OCB.